2017
DOI: 10.1159/000447153
|View full text |Cite
|
Sign up to set email alerts
|

Is Health-Related Quality of Life after Radical Cystectomy Using Validated Questionnaires Really Better in Patients with Ileal Orthotopic Neobladder Compared to Ileal Conduit: A Meta-Analysis of Retrospective Comparative Studies

Abstract: Introduction: From the most recent systematic revision of the literature, an orthotopic neobladder would seem to show marginally better health related quality of life (HR-QoL) scores compared with an ileal conduit. The aim of this study was to review all relevant published studies about the comparison between ileal orthotopic neobladder (IONB) and ileal conduit using validated HR-QoL questionnaires. Materials and Methods: Studies were identified by searching multiple literature databases. Data were synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…We found that choosing to perform a continent diversion was more frequent in younger patients, males, and those without comorbidities, treated in high-volume hospitals. This finding mirrors both the indication of a continent diversion together with a better quality of life achievable in this part of the population [15][16][17].…”
Section: Discussionsupporting
confidence: 75%
“…We found that choosing to perform a continent diversion was more frequent in younger patients, males, and those without comorbidities, treated in high-volume hospitals. This finding mirrors both the indication of a continent diversion together with a better quality of life achievable in this part of the population [15][16][17].…”
Section: Discussionsupporting
confidence: 75%
“…Actually age, gender, follow-up length and long-term complications may represent important factors affecting the impact of the type of UD on patients’ HR-QoL, when using generic, disease-specific and UD-specific questionnaires [3, 5, 11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have revealed that patients undergoing ileal neobladder surgery had better QoL than those who underwent ileal conduit [4], most of the patients who chose neobladder were younger and had less severe illness [5]. Because very few randomized controlled trials have compared the advantages of ileal neobladder surgery and traditional ileal conduit, it remains controversial whether the long-term QoL and renal function of patients after ileal neobladder surgery are better than those after traditional ileal conduit [6].…”
Section: Introductionmentioning
confidence: 99%